Spatial and Ecological Approach on Marble Mining Land in Tulungagung Regency-Indonesia: Is it Suitable as an Assessment of Disaster Mitigation Efforts? - Nur Isroatul Khusna; Sumarmi Sumarmi; Syamsul Bachri; I Komang Astina; Nevy Farista Aristin (Indonesian Journal of Geography, 2023)
Indonesia has a karst region abundant in high-quality marble mining products but is also prone to disasters. Over the years, this area has experienced numerous natural disasters, thereby leading to the need for a land suitability assessment. This is a descriptive qualitative and quantitative research with data collected from field observations, laboratory tests, interviews, and documents. Four places in the center and adjacent areas of marble producers were selected for the research sample. The data collected were analyzed using the spatial and ecological approach, fishbone, tabulation, percentage, and SWOT analysis. The result showed that numerous land mismatches contribute to the occurrence of natural catastrophes, such as improper vegetation kinds, population settlement patterns, excessive exploitation, and unfriendly human activities. This study recommends a variety of measures to improve the mining area.